Analysis of the Relationship between Age, Parity, Obesity, and Preeclampsia - Marlina, Endah Dian; Astuti, Hutari Puji; Andhikatias, Yunia Renny; Amizuar, Yulia Fauziah (Journal of Economics and Public Health, 2025)
Preeclampsia ranks among the major contributors to maternal mortality, together with bleeding and infection. This condition is characterized by hypertension and proteinuria that occurs after 20 weeks of gestation, and can cause serious complications if not treated early. This study aims to investigate the association between maternal age, parity, and obesity with the incidence of preeclampsia among pregnant women. The research method used was quantitative with a cross-sectional approach, using secondary data from medical records and analyzed univariately and bivariately using the chi-square test. The population in this study consists of all pregnant women who were recorded in the medical records or identified within the specific study period (2022–2024). Based on the context provided in the introduction, the population specifically refers to pregnant women monitored for preeclampsia risk factors (age, parity, and obesity).The total sample size used in this study is 57 pregnant women. The study utilizes secondary data derived from medical records between 2022 and 2024.The results showed that of the 19 pregnant women who experienced preeclampsia, 73.70% were in the risk age category (<20 years or >35 years), and statistical tests showed a notable association was found between age and the incidence of preeclampsia (p = 0.024; OR = 3.850). Meanwhile, there was no There is no significant relationship between parity (p = 0.851) and obesity (p = 0.255) in relation to the incidence of preeclampsia. These findings suggest that maternal age is an important risk factor that needs to be considered in efforts to prevent preeclampsia. Therefore, routine pregnancy monitoring and education about the risks of pregnancy at extreme ages are highly recommended to reduce maternal morbidity and mortality.